Impact of seasonal influenza vaccination in the presence of vaccine interference. Issue 6 (1st February 2018) - Shim, Eunha; Smith, Kenneth J.; Nowalk, Mary Patricia; Raviotta, Jonathan M.; Brown, Shawn T.; DePasse, Jay; Zimmerman, Richard K.
Highlights: Previous influenza vaccination appears to lower vaccine effectiveness. We developed an influenza transmission model with vaccination. We compared the effect of annual vaccinations and vaccination in alternate years. Annual vaccination was a still effective strategy, even with vaccine interference. Abstract: Background: Annual influenza vaccination is a key to preventing widespread influenza infections. Recent reports of influenza vaccine effectiveness (VE) indicate that vaccination in prior years may reduce VE in the current season, suggesting vaccine interference. The purpose of this study is to evaluate the potential effect of repeat influenza vaccinations in the presence of vaccine interference. Methods: Using literature-based parameters, an age-structured influenza equation-based transmission model was used to determine the optimal vaccination strategy, while considering the effect of varying levels of interference. Results: The model shows that, even in the presence of vaccine interference, revaccination reduces the influenza attack rate and provides individual benefits. Specifically, annual vaccination is a favored strategy over vaccination in alternate years, as long as the level of residual protection is less than 58% or vaccine interference effect is minimal. Furthermore, the negative impact of vaccine interference may be offset by increased vaccine coverage levels. Conclusions: Even in the presence of potential vaccine interference, our work provides a population-level perspective on the potential merits of repeated influenza vaccination. This is because repeat vaccination groups had lower attack rates than groups that omitted the second vaccination unless vaccine interference was at very high, perhaps implausible, levels.